A clutter-free home organized storage solutions and projects - Philip Schmidt (Minneapolis Creative Publishing International, Inc., 2009)
includes strategies, ideas and step-by-step how to projects that offer creative storage solutions to help control household clutter
Keywords: Storage in the home; House cleaning; Orderliness